Podocyte specific knockout of the natriuretic peptide clearance receptor is podocyte protective in focal segmental glomerulosclerosis - Liming Wang; Yuping Tang; Anne F. Buckley; Robert F. Spurney (PLoS ONE, 2025)
Natriuretic peptides (NPs) bind to glomerular podocytes and attenuate glomerular injury. The beneficial effects of NPs are negatively regulated by the NP clearance receptor (NPRC), which is highly expressed in podocytes. To determine if inhibiting NPRC is podocyte protective, we examined the effects of deleting NPRC in both cultured podocytes and in vivo. We found that: 1.Both atrial NP and C-type NP inhibit podocyte apoptosis in cultured podocytes, but these podocyte protective effects are significantly attenuated in cells expressing NPRC, and 2. Atrial NP was significantly more effective than CNP at inhibiting the apoptotic response. Consistent with the protective actions of NPs, podocyte specific knockout of NPRC reduced albuminuria, glomerular sclerosis and tubulointerstitial inflammation in a mouse model of focal segmental glomerulosclerosis. These beneficial actions were associated with: 1. Decreased expression of the myofibroblast marker alpha-smooth muscle actin, 2. Reduced expression of the extracellular matrix proteins collagen 4-alpha-1 and fibronectin, and 3. Preserved expression of the podocyte proteins nephrin and podocin. Inhibiting NP clearance may be a useful therapeutic approach to treat glomerular diseases.